2015
DOI: 10.2147/ppa.s91214
|View full text |Cite
|
Sign up to set email alerts
|

“I wish they could be in my shoes”: patients’ insights into tertiary health care for type 2 diabetes mellitus

Abstract: BackgroundInsightful accounts of patient experience within a health care system can be valuable for facilitating improvements in service delivery.ObjectiveThe aim of this study was to explore patients’ perceptions and experiences regarding a tertiary hospital Diabetes and Endocrinology outpatient service for the management of type 2 diabetes mellitus (T2DM).MethodNine patients participated in discovery interviews with an independent trained facilitator. Patients’ stories were synthesized thematically using a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Patients indicated that they first needed to accept their situation. After acceptance they realized that they needed to take charge of their own health and care process [22,25,31,46,61,64,66,72,77,80,84,102].…”
Section: Resultsmentioning
confidence: 99%
“…Patients indicated that they first needed to accept their situation. After acceptance they realized that they needed to take charge of their own health and care process [22,25,31,46,61,64,66,72,77,80,84,102].…”
Section: Resultsmentioning
confidence: 99%
“…Physician empathy is associated with blood glucose control (25) and a lower incidence of acute metabolic complications (26). However, many patients say their providers show little empathy or understanding of their struggle to manage diabetes (27,28). …”
Section: The Patient-provider Relationshipmentioning
confidence: 99%
“…Patient-provider collaboration hinges on effective communication (29). Unfortunately, many patients struggle to understand what their providers tell them, yet are reluctant to tell their provider when they feel confused (27). This reluctance is exacerbated for patients with low health literacy, who may feel ashamed of their literacy skills and try to hide their lack of understanding (2).…”
Section: The Patient-provider Relationshipmentioning
confidence: 99%
See 2 more Smart Citations